Case report: Strong low-density-cholesterol reduction accompanied by shrinkage of low-attenuation coronary plaque during lipid-lowering treatment with bempedoic acid: serial evaluation by coronary computed tomography angiography - Korosoglou, Grigorios; Giesen, Alexander; Geiss, Eva; Stach-Jablonski, Ksenija (Frontiers in Cardiovascular Medicine, 2023)
Here, we present a patient with coronary artery disease and prior percutaneous coronary interventions. This patient had to discontinue taking multiple statins and ezetimibe due to intolerance with musculoskeletal complaints and nausea. Monotherapy with bempedoic acid was well tolerated and was exceptionally effective at lipid lowering, enabling patients to achieve the low-density lipoprotein target of <55 mg/dl, as recommended by current guidelines. In addition, serial coronary computed tomography angiography performed upon clinical indications, during 20 months of lipid-lowering treatment with bempedoic acid, demonstrated signs of favorable plaque component modification, with shrinkage of the low-attenuation plaque component compared to baseline findings.